Fis binding in the dnaA operon promoter region. - Froelich, J M (1996)
The region between the rpmH and dnaA genes contains five promoters that divergently express the ribosomal protein L34 and the proteins of the dnaA operon, including DnaA, the beta clamp of DNA polymerase III holoenzyme, and RecF. The DNA-binding protein Fis was shown by the band shift assay to bind near the rpmHp2 and dnaAp2 promoters and by DNase I footprinting to bind to a single site in the dnaAp2 promoter overlapping the -35 and spacer sequences. There were no observable differences in Fis affinity or the angle of bending induced by Fis between methylated and unmethylated DNA fragments containing the Fis binding site in the dnaAp2 promoter. Fis directly or indirectly represses the expression of DnaA protein and the beta clamp of DNA polymerase III. A fis null mutant containing a dnaA-lacZ in-frame fusion had twofold greater beta-galactosidase activity than a fis wild-type strain, and induced expression of Fis eliminated the increase in activity of the fusion protein. A two- to threefold increase in the levels of DnaA and beta clamp proteins was found in a fis null mutant by immunoblot gel analysis.